Effectiveness analysis of impact location algorithm for composite reinforced structures - ZHANG Yang; YANG Yu; QI Ge; ZHANG Sheng (Hangkong gongcheng jinzhan, 2023)
With the large-scale application of composite materials in aircraft structures, the threat of visually invisible damage such as internal delamination of composite materials caused by impact from foreign objects is increasing,therefore, impact event monitoring and impact location identification of composite reinforced structures is essential.In order to verify the engineering validity of the impact localization algorithm, based on the piezoelectric sensing signal of the impact test on the composite large wall plate structure, the localization accuracy of the time-reversal focusing,error function and cross-correlation function impact monitoring algorithms is compared. The results show that, in the monitoring area of 2 360 mm×1 260 mm, the error of the cross-correlation function algorithm is smaller than that of the time-reversal focusing algorithm, and the error of the time-reversal focusing algorithm is larger at the truss, which is not suitable for impact positioning of reinforced structures.